Patient Participation in Pro Re Nata Medication in Forensic Psychiatric Care: Interview Study with Patients and Nurses - Hipp Kirsi; Kangasniemi Mari (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Pro re nata (PRN, as-needed) medication is commonly used in forensic psychiatric inpatient care, but little is known about the participation of patients in its prescription and administration. This study describes patient participation in PRN medication treatment in forensic psychiatric inpatient care. Data were collected during interviews with 34 inpatients and 19 registered nurses in a Finnish forensic psychiatric hospital. The data underwent inductive content analysis. We found that patient participation in PRN was related to patients' individual needs and health conditions, and the use of PRN involved private decisions made in the social context of the ward. PRN was an integrated part of daily care, and it involved three stakeholders, namely patients, nurses, and physicians; however, the role of patients in this collaboration was undefined. The administration events for PRN were multiform, and depended on the level of agreement between patients and nurses on the need for PRN. In the future, more attention should be paid to how to motivate patients and provide them with equal opportunities to be involved in the planning of PRN, and to optimize shared decision making so that the expertise of both patients and nurses is utilized in the administration and evaluation of PRN.